Análise imaginológica das estruturas de suporte dentário após a expansão rápida da maxila em crianças em longo prazo - Bento, Patrícia Fabíola Lizarelli (2015)
Objective: to evaluate the tooth supporting structures after rapid maxillary expansion, by image analysis, in the long term. Material and methods: the study was conducted on 10 individuals (5 females and 5 males), with mean age 9.41 (s.d. 2.13) at treatment onset (stage T1), with Class I or II malocclusions presenting skeletal atresia of the maxillary dental arch, possible presence of unilateral or bilateral posterior crossbite, treated with rapid maxillary expansion using a toothtissue-borne Haas expander. The activation protocol comprised one complete turn per day, until 7 mm of expansion was achieved. Cone-beam computed tomographies were obtained before expansion, stage T1, and after a mean period of 1.48 (s.d. 0.19), stage T2, with mean age 10.88 (s.d. 2.16), for long-term evaluation of changes occurring in tooth supporting structures: bone plate thickness, bone crest level, inclination of maxillary first molars and intermolar transverse dimension. The changes occurring between stages T1 and T2 were compared by the paired t test, and gender dimorphism was assessed by the t test. Results: the buccal bone plate thickness of the maxillary right first molar, mesial root (- 0.91mm) and distal root (-0.54 mm) were reduced, as well as in the maxillary left first molar, mesial root (-1.01mm) and distal root (-0.40 mm). There was increase in the transverse dimension of 3.85 mm and no gender dimorphism was observed. Conclusion: there was no correlation between the increase in transverse dimension and the degree of inclination of maxillary first molars, demonstrating the bone gain, with minimum changes in the buccal alveolar process of maxillary right and left first molars and the stability of transverse changes achieved.